MENUMBUHKAN GREEN BEHAVIOUR SISWA MELALUI STRATEGI TANDUR BERBASIS PROYEK DALAM PEMBELAJARAN IPS - Ria Kurniasari; Windu Mandela (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2019)
The research was motivated by researchers' concerns about the low green behaviour of students. To realize green behaviour as a character, the researcher applied Tandur strategy (Grow, Natural, Name, Demonstrate, Repeat, and Celebrate) based on project. Tandur is one of the learning models that will provide direct experience to students and make the material real. Furthermore, project-based learning is a learning activity that gives freedom to explore and produce a work from the learning process. In this case something that was project based could integrate several branches of science such as the demands of the current curriculum, namely thematic learning. The research method used was Classroom Action Research (CAR) with the Kemmis Taggart design which consists of four stages: planning, implementation, observation and reflection. The instruments used were observation sheets, interview sheets and also evaluation sheets. Overall Tandur strategy based on the project had a positive impact on students' green behaviour. This was obtained from the improvement of various aspects, both aspects of knowledge, behaviour which consists of conscience and application/ action, and also from aspects of student projecting. Thus it could be concluded that Tandur strategy based on project could improve students' green behaviour.